2014
DOI: 10.1007/s10661-014-3770-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of cadmium and lead in residents near abandoned metal mine areas in Korea

Abstract: We analyzed national data on blood lead levels (BLL) and blood cadmium levels (BCL) in residents living near 38 abandoned metal mining areas (n = 5,682, 18-96 years old) in Korea that were collected by the first Health Effect Surveillance for Residents in Abandoned Metal mines (HESRAM) from 2008 to 2011. The geometric mean BCL and BLL were 1.60 μg/L (95 % CI = 1.57-1.62 μg/L) and 2.87 μg/dL (95 % CI = 2.84-2.90 μg/dL), respectively, notably higher than levels in the general population in Korea and other countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
2
7
2
Order By: Relevance
“…Moreover, there were significant correlations between the concentrations of some elements in different tissues; for instance, the contents of Se, As, Cr and Ni in hair were significantly positively correlated to those in blood. For Cd, an insignificant correlation was found between hair and blood concentrations, which suggested that hair Cd concentration is relatively independent of the Cd level in the blood, in agreement with earlier studies in cows (Rogowska et al, 2009;Patra et al, 2007). Although further research is necessary, the concentrations of the same elements in different tissues could indicate mutual reflectance and be complementary for assessment of corresponding heavy metal exposure, as was also suggested in human studies (Xing et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, there were significant correlations between the concentrations of some elements in different tissues; for instance, the contents of Se, As, Cr and Ni in hair were significantly positively correlated to those in blood. For Cd, an insignificant correlation was found between hair and blood concentrations, which suggested that hair Cd concentration is relatively independent of the Cd level in the blood, in agreement with earlier studies in cows (Rogowska et al, 2009;Patra et al, 2007). Although further research is necessary, the concentrations of the same elements in different tissues could indicate mutual reflectance and be complementary for assessment of corresponding heavy metal exposure, as was also suggested in human studies (Xing et al, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…A multivariate analysis confirmed that sex, age, and smoking habit significantly influence urine Cd, and we also made the analysis to detect whether the blood Cd level was associated with gender and age [17]. No statistically significant differences were found in different gender and age groups in this study, perhaps because the quantity of samples was relatively limited [18]. Diet and drinking water are identified as the primary sources of Cd exposure in the general populations [19].…”
Section: Discussionsupporting
confidence: 55%
“…The blood Cd concentrations of the 5682 residents living near the 38 abandoned metal mines in Korea were found to be 1.60 μg/L, and those of the residents living within a 2 km radius of the abandoned mine were found to be 1.87 μg/L, which are higher than those of the residents living outside of the 2 km radius (1.31 μg/L) (Park et al 2014). The blood Cd concentration of the US general population aged ≥20 years was 0.36–0.47 μg/L (CDC CDC 2009), while that of the Canadian general population aged ≥20 years was 0.35–0.49 μg/L.…”
Section: Resultsmentioning
confidence: 99%
“…Residents living near the abandoned metal mines were people aged ≥65 years who had lived in the area for 40 years or longer (Park et al 2014). There is a high likelihood that residents have been exposed to the pollutants as they have resided in the areas for a long time after development and abandonment of the mines.…”
Section: Introductionmentioning
confidence: 99%